Loco-regional deep hyperthermia combined with intravesical Mitomycin instillation reduces the recurrence of non-muscle invasive papillary bladder cancer. (1st January 2021) - Wen, Yu-Ching; Lee, Liang-Ming; Lin, Yung-Wei; Syu, Syuan-Hao; Lin, Ke-Hsun; Fan, Yen-Chun; Lee, Hsin-Lun; Lai, Benjamin Chung Howe; Shih, Hung-Jen
Abstract: Objectives: To compare the therapeutic effects of locoregional deep hyperthermia combined with intravesical chemotherapy with those of intravesical chemotherapy alone in patients with intermediate-/high-risk non-muscle invasive bladder cancer (NMIBC). To evaluate the impact of thermal dose in hyperthermia treatment. Methods: We analyzed data retrieved from the medical records of patients with intermediate-/high-risk NMIBC treated with intravesical mitomycin (IM group) or locoregional deep hyperthermia combined with intravesical mitomycin (CHT group) at a single tertiary care hospital between May 2016 and June 2019. The primary and secondary endpoints were the recurrence-free survival rate and progression-free survival rate, respectively. Thermal dose was evaluated and adverse events were also recorded. Results: In total, 43 patients (CHT: 18 patients, IM: 25 patients) were enrolled. The median follow-up durations were 14 and 23 months, respectively. The recurrence rate at 12 months was significantly lower in the CHT group than in the IM group (11.1% vs. 44%, p = .048); this trend persisted at 24 months (CHT: 11.1%, IM: 48%; p = .027). The recurrence-free survival was also significantly higher in the CHT group than in the IM group ( p = .028). No tumor recurrence was noted in patients who received a thermal dose of ≥4 CEM43. All adverse events were well tolerated, and there was no treatment-related mortality. Conclusions: Intravesical chemotherapy combined with locoregional deep hyperthermia for intermediate-/high-risk papillary NMIBC can significantly decrease the recurrence rate relative to that observed after intravesical chemotherapy alone.